Inconstitucionalidade: uma qualidade graduável dos atos jurídicos - Santos, Victor Fentanes Guimarães (2011)
This work aims to examine the complexity of the establishment of the legal effectiveness of the unconstitutional legal act according to the systematic nature of the legal system, which implies the need of taking into consideration all of the legal norms as a whole. The characterization of the legal system takes into consideration the plan of the Science of Law and the Objective Law, the characteristics that each one of these systems presents and the arrangement of constitutionality in this context are indicated in this paper. As it is important for the understanding of this matter, it is made a distinction between existence, validity and effectiveness of legal acts, pointing and indicating the issue of constitutionality in this context. The study describes parameters for the analysis of the unconstitutionality and the legal acts subjected to this investigation of parameters. The partial omission; the progressive unconstitutionality; the unconstitutionality in the practical case and other similar situations will be determined and studied as examples of situations that demonstrate the complexity of the definition of the effectiveness of the unconstitutional legal acts. All this research allows us to assume that the legal consequences of unconstitutionality depend on the degree of incompatibility that the analyzed act features according to the Constitution as a whole, not taking into consideration only the supposed constitutional norm infringed.